2009
DOI: 10.1177/1010539509341423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Work-Related Upper Limbs Symptoms (WRULS) Among Office Workers

Abstract: An analytical cross-sectional study was carried out to determine the prevalence of work-related upper limbs symptoms (WRULS) among office workers and factors associated with it. A self-administered questionnaire was used to collect the information. A total of 463 (87.7%) office workers from selected government agencies participated in this study. The mean age of the respondents was 34.1 years (range = 18-55 years). Majority (91.6%) were Malay and female (72.8%), and 58.1% were from clerical group. Mean duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…3 Meanwhile, investigations proved that the use of computers for more than 3 hours per day intensifies the incidences of CVS 3 -5 and it is a major occupational epidemic of the 21st century. 6,7 The effects of CVS on users’ health can be expressed in terms of musculoskeletal, 8 psychological, 9 physiological, 10 occupational productivity, 11 and quality of life (QoL) as well as visual comfort. 5 This leads to lower employee work efficiency, loss of productivity, a higher rate of errors, worse job satisfaction, and a lower quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…3 Meanwhile, investigations proved that the use of computers for more than 3 hours per day intensifies the incidences of CVS 3 -5 and it is a major occupational epidemic of the 21st century. 6,7 The effects of CVS on users’ health can be expressed in terms of musculoskeletal, 8 psychological, 9 physiological, 10 occupational productivity, 11 and quality of life (QoL) as well as visual comfort. 5 This leads to lower employee work efficiency, loss of productivity, a higher rate of errors, worse job satisfaction, and a lower quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of upper limb symptoms reported among Malaysian office workers (34%) and its association to computer use, [11] while low back pain among Malaysian teachers (40%) was associated with physical activity [12]. A recent study [13] investigated the prevalence of MSP among Malaysian college students and its relationship to computer use.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on clerical public servants reported 33% (95% confidence interval = 28.8-37.3) prevalence of upper limb symptoms. 30 The other study, which was conducted among secretarial staff and undergraduate students, reported that poorer workstation ergonomics increased the risk of developing neck, back, and wrist disorders. 31…”
mentioning
confidence: 99%